Strategi Pengembangan Model Inovasi Akta Kelahiran Online di Kota Bandung - Putri Wulandari; Yunni Susanty (Jurnal Transformasi Administrasi, 2016)
The innovation of the Birth Certificate Online is an innovation for birth certificates process through an online application. This innovation enables the public to submit the application of birth certificate through the website. The utilization of this innovation was still low when this study conducted comparing the number of manual application at Disdukcapil's office in Bandung. The low utilization of the Birth Certificate Online service was caused by many things, both internal and external conditions. This study suggests eight possible strategies that must be considered in order to increase the utilization of this innovation. They are the source of funds, the execution time of service, the collaboration /partnerships, the methods of dissemination, the implementation mechanism innovation, the executive, and the infrastructure.